Microbiome and Cancer in the Oral Cavity: A Bioinformatics Perspective - Yu-Cheng Lin; Ding-Han Wang; Cheng-Chieh Yang; Ming-Lun Hsu (Journal of Multidisciplinary Dental Research)
The relationship between microbiome and cancer in the oral cavity has been under intense scrutiny over the past decade due to the advancement in next-generation sequencing. However, rapid accumulation of sequencing data may yield more questions than answers. Although such inconclusiveness can be attributed to the heterogeneous nature of biological phenomena, inconsistency in complex bioinformatics analysis may also play a role. In this review, we aim to provide a comprehensive and concise overview of common bioinformatics analysis processes used in microbiome studies focusing on 16S rDNA sequencing. By taking this bioinformatics perspective as a conceptual framework, we further discussed the consistency and discrepancies among numerous studies on the relationship between oral microbiome and oral cancer. This review aims to elucidate the bioinformatics methodologies and their impact on the current understanding of the oral microbiome's role in cancer development.